The Effect of Zeolite Na-X and Clinoptilolite as Functional Fillers on the Mechanical, Thermal and Barrier Properties of Thermoplastic Polyurethane - Nello Russo; Letizia Verdolotti; Giuseppe Cesare Lama; Federica Recupido; Barbara Liguori; Maria Oliviero (Molecules)
To obtain sustainable food packaging materials, alternatives to traditional ones must be researched. In this work, two different kinds of zeolites, i.e., a natural one, Clinoptilolite, and a synthetic one, Zeolite Na-X, were mixed with thermoplastic polyurethane for the fabrication of composites. Composite films were prepared via a hot mixing stage and then by means of a hot compression molding process. Several TPU/zeolite composites were produced with a filler concentration ranging from 5% to 10%wt. Finally, the obtained films were characterized by Fourier Transform Spectroscopy (FT-IR, ATR), thermal analysis (TGA and DSC), frequency sweep test, scanning electron microscopy (SEM), mechanical tensile test and oxygen permeability test. For both fillers and at all concentrations, the inclusion of zeolites significantly influenced the analyzed properties. In the TPU/zeolite composites, an overall enhancement was observed compared to the neat polymer, attributed to improved processability, superior barrier properties and the potential to create active materials by loading zeolite combined with various chemicals for specific applications. These findings suggest that the resulting composites hold considerable promise for applications in the food packaging sector.